VaERD15, a Transcription Factor Gene Associated with Cold-Tolerance in Chinese Wild Vitis amurensis - Yu, Dongdong; Zhang, Lihua; Zhao, Kai; Niu, Ruxuan; Zhai, Huan; Zhang, Jianxia (Frontiers in Plant Science, 2017)
Early responsive to dehydration (ERD) genes can be rapidly induced to counteract abiotic stresses, such as drought, low temperatures or high salinities. Here, we report on an ERD gene (VaERD15) related to cold tolerance from Chinese wild Vitis amurensis accession ‘Heilongjiang seedling’. The full-length VaERD15 cDNA is 685 bp, including a 66 bp 5′-untranslated region (UTR), a 196 bp 3′-UTR region and a 423 bp open reading frame encoding 140 amino acids. The VaERD15 protein shares a high amino acid sequence similarity with ERD15 of Arabidopsis thaliana. In our study, VaERD15 was shown to have a nucleic localization function and a transcriptional activation function. Semi-quantitative PCR and Western blot analyses showed that VaERD15 was constitutively expressed in young leaves, stems and roots of V. amurensis accession ‘Heilongjiang seedling’ plants, and expression levels increased after low-temperature treatment. We also generated a transgenic Arabidopsis Col-0 line that over-expressed VaERD15 and carried out a cold-treatment assay. Real-time quantitative PCR (qRT-PCR) and Western blot analyses showed that as the duration of cold treatment increased, the expression of both gene and protein levels increased continuously in the transgenic plants, while almost no expression was detected in the wild type Arabidopsis. Moreover, the plants that over-expressed VaERD15 showed higher cold tolerance and accumulation of proline, soluble sugars, proteins, malondialdehyde and three antioxidases (superoxide dismutase, peroxidase, and catalase). Lower levels of relative ion leakage also occurred under cold stress. Taken together, our results indicate that the transcription factor VaERD15 was induced by cold stress and was able to enhance cold tolerance.